ETHNOBOTANICAL SURVEY OF MEDICAL PLANT USED FOR THE TREATMENT OF HYPERTENSION IN SUBULUSSALAM SUB-DISTRICT ACEH, INDONESIA - Hasanuddin Hasanuddin; Djufri Djufri; Kusyanti Kusyanti; Nazaruddin Nazaruddin (Biotik, 2021)
This research is intended to know the types of plants, parts, how to care and its use for hypertension disease drugs in the community in Rundeng of Subulussalam City. Data collection is done by interview and observation. Data analysis was done descriptively ie data in table form. The results of the study found 22 species of plants, consisting of 21 genus, 18 families as hypertension drugs used by the community in Rundeng of Subulussalam City. The use of plant parts that are used as hypertension drugs are all parts of plant organs, the leaves are the most widely used parts. The most dominant way to use it is by boiling it, in a blender and then drinking the water. The most dominant way to use plants for medicine is by drinking and eating as fresh vegetables.